2022
DOI: 10.1590/0103-8478cr20210417
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Brazilian wheat cultivars to blast under controlled condition

Abstract: The first report of wheat blast in the world was in Brazil, in 1986. Since then, a great effort has been made towards the development of wheat cultivars resistant to this disease, which is caused by the fungus Pyricularia oryzae Triticum (PoT). The objective of this research was to (i) evaluate the resistance of wheat genotypes to blast and (ii) verify the correlation between disease severity on wheat spikes and sporulation rate of PoT on spike rachises. Plants of 40 cultivars grown in pots, at the flowering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Severity considers both the diseased and healthy tissues, while I summarize only the presence or absence of symptoms on a sample, regardless of the severity (Bock et al, 2021. Therefore, S can vary considerably for a specific value of I, especially for I greater than 30% in blast epidemics, as established in a previous study (dos Santos et al, 2022). Also, When evaluating the reaction of several cultivars to wheat head blast, the authors of one study observed that the cultivars with the greatest I did not always present the greatest yield losses (Dianese et al, 2021).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Severity considers both the diseased and healthy tissues, while I summarize only the presence or absence of symptoms on a sample, regardless of the severity (Bock et al, 2021. Therefore, S can vary considerably for a specific value of I, especially for I greater than 30% in blast epidemics, as established in a previous study (dos Santos et al, 2022). Also, When evaluating the reaction of several cultivars to wheat head blast, the authors of one study observed that the cultivars with the greatest I did not always present the greatest yield losses (Dianese et al, 2021).…”
Section: Discussionmentioning
confidence: 75%
“…In some studies on the relationship between disease and yield, the resistance of the cultivar is an important source of variation in the intensity of the blast in the experiment either under natural epidemics or artificial ones. The cultivars utilized in other works show a broader classification of blast reaction (Coelho et al, 2016;Gomes et al, 2017;Maciel et al, 2022). However, in the trials conducted to generate our data, the main source of variation in wheat head blast intensity was due to varying planting dates, a fact that may have reduced any possible influence of the varietal resistance of the three cultivars evaluated in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation